Perception towards Cervical Cancer Insurance Policy: A Study on Women in Barishal City (Global Journal of Management and Business Research, 2024)
The purpose of this research paper is to assess the perception of urban women towards having an insurance policy as a precaution against cervical cancer Data required for the research have been collected from primary data source taking into consideration total 170female as respondents who have been living in Barishal city with at least 18 years old Frequency distribution has been used to explain the response of 27 questions comprising demographic and financial aspect of the respondents Reliability of the survey has been tested by Cronbach s Alpha with satisfied value of more than 0 705 Moreover a regression analysis has been used for finding out the most significant factors influencing the willingness of purchasing cervical cancer insurance policy in near future covering 7relevant variables Overall it has been found that approximately 23 respondents from the surveyed sample has a history to be encountered with cervical problems like ovarian cyst uterus infection etc However most of them neither had any screening nor have any health insurance policy as a precaution against cancer Moreover significant number of participants are willing to purchase a cancer insurance policy if it is with a very reasonable premium
Keywords: cervical cancer insurance policy; screening; social awareness; motivation